A meta-analysis of management effects on forest carbon storage. (3rd July 2016) - Kalies, Elizabeth L.; Haubensak, Karen A.; Finkral, Alex J.
ABSTRACT: Forest management can have substantial impacts on ecosystem carbon storage, but those effects can vary significantly with management type and species composition. We used systematic review methodology to identify and synthesize effects of thinning and/or burning, timber harvesting, clear-cut, and wildfire on four components of ecosystem carbon: aboveground vegetation, soil, litter, and deadwood. We performed a meta-analysis on studies from the United States and Canada because those represented 85% of the studies conducted worldwide. We found that the most important variables in predicting effect sizes (ratio of carbon stored in treated stands versus controls) were, in decreasing order of importance, ecosystem carbon component, time since treatment, and age of control. Management treatment was the least important of all the variables we examined, but the trends we found suggest that thinning and/or burning treatments resulted in less carbon loss than wildfire or clear-cut. This finding is consistent with recent modeling studies indicating that forest management is unimportant to long-term carbon dynamics relative to the effects of large-scale natural disturbances (e.g., drought, fire, pest outbreak). However, many data gaps still exist on total ecosystem carbon, particularly in regions other than North America, and in timber production forests and plantations.